Can Artificial Intelligence Perform Ijtihad? Authority, Epistemology, and Legitimacy in Digital Islamic Jurisprudence - Ahmed, Alwy; Masuwd, Mowafg; Sabir, Muhammad Rehan; Mahmudulhassan, Mahmudulhassan (Suhuf: International Journal of Islamic Studies, 2026)
Background: Artificial intelligence (AI) can rapidly search juristic sources, compare legal opinions, and generate structured arguments. Yet its fluency may obscure the distinction between computational capability and legitimate authority in Islamic jurisprudence. Objective: This study examines whether AI can independently perform ijtihad and identifies conditions for its responsible use without displacing human juristic authority. Methodology: A structured normative-doctrinal approach integrates classical usul al-fiqh and fatwa doctrine with scholarship on generative AI, algorithmic accountability, and AI governance. Analysis applies five criteria: source competence, methodological reasoning, contextual judgment, moral agency, and answerability. Results: Current AI systems satisfy only instrumental aspects of source competence and methodological reasoning. They can retrieve sources, map disagreements, identify analogies, and organize preliminary arguments, but cannot possess legally recognized intention, bear taklif, assume responsibility for harm, or receive juristic authorization. The study proposes a five-layer Augmented ijtihad Model: source retrieval, doctrinal mapping, inferential support, contextual and maqasid evaluation, and final authorization. Conclusion: AI can strengthen ijtihad but cannot function as an independent mujtahid. Implication: Islamic legal institutions should require verified databases, school-of-law tagging, uncertainty disclosure, qualified human review, audit trails, contestability, and post-deployment monitoring, positioning AI as accountable research infrastructure under scholarly supervision rather than autonomous religious authority